Transportation of patients in medical vehicles - Problems and comfort solutions - Mikulić, Dinko; Mück, Draško; Spudić, Robert (Crisis Management Days, 2024)
Medical vehicles are produced on the basis of cargo vans, transporters. Such vehicles, without adequate modifications, do not offer comfort necessary for transport of patients. Harmful body vibrations cause discomfort and can worsen the condition of the patient lying on the stretcher. The patient is not protected and cannot receive adequate care due to the vibrations. The research problem lies in the suspension of such vehicles, which is intended for the transport of cargo and is not adapted for the transport of sick and injured or hospitalized patients. The experiences of patients when transported over long distances bring desperate stories. Severe bounces, vibrations, shocks, jolts and side-to-side rolling of the vehicle can not only cause secondary injuries to patients, but can also affect the use of instruments and equipment in the vehicle. The paper presents the method of installing such a suspension in a medical vehicle. By replacing the old metal spring with an active air bellow, harmful vibrations are reduced and eliminated, thus increasing the comfort of transporting patients with medical vehicles.